Professional development in English for specific purposes: designing the curriculum of an online ESP teacher education course - Kakoulli-Constantinou, Elis; Papadima-Sophocleous, Salomi (My University, 2021)
Despite the developments in the English for Specific Purposes (ESP) field, the field of ESP Teacher Education (TE) remains neglected. Research in the area of ESP TE has not been given much attention, and the opportunities ESP practitioners have for Professional Development (PD) are very limited. This chapter describes the development of a curriculum for an online ESP TE course, the ReTEESP Online. The process occurred in the context of a Technical Action Research (TAR) study, the purpose of which was to address the needs of a group of 24 language instructors in terms of ESP TE. The course was based on a literature review in ESP and ESP TE, including learning theories and TE models, and recent developments in curriculum design. The course was also informed by an analysis of the 24 language instructors’ needs in ESP TE and a pilot implementation of the course.
Keywords: English for Specific Purposes; Teacher education; Professional development; Curriculum development; Needs analysis; Social constructivism; Cloud technologies; Connectivism